Band Rejections for WLAN and WIMAX Utilizing UWB Planar Antenna by Slits in the Conductor Elements - Jainal, Siti Fatimah; Mohamed, Norliza; Hamzah, Azura (International Journal of Integrated Engineering, 2020)
Band rejections for WLAN and WIMAX frequency bandwidths are realized in a UWB planar antenna utilizing a single slit in an elliptical element. WLAN and WIMAX communication system frequency bandwidths have been known to coexist with the UWB frequency bandwidth. Coexistence of multiple frequency bandwidths are susceptible to disadvantage and could cause interferences to other communication system. The disadvantages could be in form of signal disruption, data loss and equipment malfunctions [1-3]. Thus, it is essential to eliminate WLAN frequency bandwidth from the UWB communication system. Slits are employed to influence the exterior current distribution on the radiator and therefore, has generated mismatched of the input impedance. The phenomenon has caused the band notch characteristic and thus, rejected the frequency bandwidths for 5 to 6 and 3.3 to 3.7GHz, respectively. The structures of the slits are simple in a compact design of the UWB planar antenna. The UWB planar antennas with band rejections are compared with the reference antenna. The reflection coefficients S11 for the designed UWB planar antennas have rejected the frequency bandwidths for 5 to 6 and 3.3 to 3.7GHz, consecutively. The peak of the notched-band reflection coefficient S11 for the frequency bandwidths 5 to 6 and 3.3 to 3.7GHz are about -3 and -4dB, respectively. Surface currents are distributed in the slit areas. The radiation patterns are illustrated for the frequency 3.5, 7.5 and 9.5GHz for the single notched-band, while 4.5, 7.5 and 9.5GHz for the dual notched-band characteristics. Radiation patterns for the single and dual notched-band in the H- and E-planes for the designed antennas are in omni- and bi-directional, respectively. Maximum gains G are in the –z and –x direction in the H- and E- plane, for the UWB planar antenna with single and dual notched-band characteristics.